Ptk7 and Mcc, Unfancied Components in Non-Canonical Wnt Signaling and Cancer - Norris Ray Dunn (Cancers, 2016)
Human development uses a remarkably small number of signal transduction pathways to organize vastly complicated tissues. These pathways are commonly associated with disease in adults if activated inappropriately. One such signaling pathway, Wnt, solves the too few pathways conundrum by having many alternate pathways within the Wnt network. The main or “canonical” Wnt pathway has been studied in great detail, and among its numerous downstream components, several have been identified as drug targets that have led to cancer treatments currently in clinical trials. In contrast, the non-canonical Wnt pathways are less well characterized, and few if any possible drug targets exist to tackle cancers caused by dysregulation of these Wnt offshoots. In this review, we focus on two molecules—Protein Tyrosine Kinase 7 (Ptk7) and Mutated in Colorectal Cancer (Mcc)—that do not fit perfectly into the non-canonical pathways described to date and whose roles in cancer are ill defined. We will summarize work from our laboratories as well as many others revealing unexpected links between these two proteins and Wnt signaling both in cancer progression and during vertebrate and invertebrate embryonic development. We propose that future studies focused on delineating the signaling machinery downstream of Ptk7 and Mcc will provide new, hitherto unanticipated drug targets to combat cancer metastasis.